2005
DOI: 10.3928/1542-8877-20050301-04
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia and the Risks of Intraocular Surgery

Abstract: * BACKGROUND AND OBJECTIVE: In thrombocytopenia, a hemorrhagic diathesis is usually present due to a low platelet count and has been related to the development of cataracts and retinopathy. The concomitant administration of nonsteroidal anti-inflammatory drugs can increase the hemorrhagic diathesis. The purpose of this study was to investigate the impact of thrombocytopenia during and after intraocular surgery. * PATIENTS AND METHODS: A retrospective study of medical files of patients who had undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Haemorrhagic episodes, including intracranial haemorrhage, are long‐term complications of ITP, . In other studies, postoperative bleeding was noted as a major complication in patients with ITP after splenectomy and minor procedures, , but not cardiac operations. Studies in non‐surgical settings have associated ITP with risk of thromboembolism, , .…”
Section: Discussionmentioning
confidence: 97%
“…Haemorrhagic episodes, including intracranial haemorrhage, are long‐term complications of ITP, . In other studies, postoperative bleeding was noted as a major complication in patients with ITP after splenectomy and minor procedures, , but not cardiac operations. Studies in non‐surgical settings have associated ITP with risk of thromboembolism, , .…”
Section: Discussionmentioning
confidence: 97%
“…8,9 Previous studies of patients with thrombocytopenia undergoing large-incision cataract surgeries or combination cataract extraction and glaucoma surgery have raised concerns about an increased risk for perioperative bleeding. 3 A small retrospective review of 6 cases of thrombocytopenic patients undergoing phacoemulsification did not identify any bleeding complications; however, it is limited by the small sample size. 4 Other studies of suprachoroidal hemorrhage, a sight-threatening complication of cataract surgery, have not identified thrombocytopenia as a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…2 A more recent 2005 study analyzed both cataract and glaucoma procedures and concluded that thrombocytopenia carried an increased risk for perioperative bleeding after ocular surgery, with bleeding complications in 2 of 11 cases: 1 trabeculectomy with retrobulbar anesthesia and 1 cataract surgery with peribulbar anesthesia. 3 The risk for bleeding in clear corneal incision cataract surgeries is presumably lower than that in extracapsular cataract extraction or glaucoma procedures, given the avascular nature of the cornea and crystalline lens. Although 2 case reports described intraoperative occurrences of iris and suprachoroidal hemorrhages during clear corneal incision cataract surgery, with reported platelet counts of 75.0 and 30.0 × 10 3 /μL, respectively.…”
mentioning
confidence: 99%
“…There are bleeding risks in those patients during or following the surgery. 10 Baas et al have shown that PDT may be combined with other techniques such as surgery with great success. Nevertheless, the PDT alone with adequate lesion penetration can also promote excellent outcome.…”
Section: Discussionmentioning
confidence: 99%